Familial vitiligo in mother and child; the genetic theory connection - Muphy M. Oripelaye; Olayinka A. Olasode; Olaniyi Onayemi; Olatunde F. Olanrewaju (Our Dermatology Online, 2017)
Vitiligo is an acquired loss of skin pigment of unknown etiology. It frequently occurs in familial clusters thereby favoring the genetic theory for its pathogenesis. Several genes have been described in association with vitiligo and it is often thought to be polygenic with variable expressivity. We present two cases of familial vitiligo occurring in a mother and her child with a more severe presentation in the child. These cases of familial vitiligo portray the genetic theory with associated features suggesting genetic anticipation.